2016
DOI: 10.1128/genomea.01235-16
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of the Oleaginous Yeast Cryptococcus curvatus ATCC 20509

Abstract: Cryptococcus curvatus ATCC 20509 is a commonly used nonmodel oleaginous yeast capable of converting a variety of carbon sources into fatty acids. Here, we present the draft genome sequence of this popular organism to provide a means for more in-depth studies of its fatty acid production potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…In this regard, transcriptome data can provide a good basis for predicting introns. We therefore collected transcriptome data (RNAseq) of C. oleaginosus ATCC 20509 from two conditions and used it to structurally annotate genome sequence MATS00000000.1 of C. oleaginosus ATCC 20509 [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, transcriptome data can provide a good basis for predicting introns. We therefore collected transcriptome data (RNAseq) of C. oleaginosus ATCC 20509 from two conditions and used it to structurally annotate genome sequence MATS00000000.1 of C. oleaginosus ATCC 20509 [28].…”
Section: Resultsmentioning
confidence: 99%
“…The genome sequence MATS00000000.1 from Cutaneotrichosporon oleaginosus ATCC 20509 reported by [28] was annotated and used to build the model. The genome sequence has 19.86 Mbp and a GC content of 60.7%.…”
Section: Genome Sequencementioning
confidence: 99%
“…Since 2015, genome sequences have been published for Trichosporonales species from the genera Apiotrichum, Cutaneotrichosporon, Takashimella, Trichosporon, and Vanrija [45][46][47][48][49][50][51][52] ( Table 1). We analyzed the genomes of 29 isolates that belong to 24 Trichosporonales species for the organization of the MAT loci, and found that all of them contain fused MAT loci, with both mating-type determining genes (STE3 and SXI) located ~55 kb apart from each other.…”
Section: Trichosporonales Species Have Fused Hd and P/r Mating Type Locimentioning
confidence: 99%
“…Recently, several Trichosporonales were studied with respect to their biotechnological properties, including the oil-accumulating C. oleaginosum, which was first isolated from a dairy plant, and has the ability to metabolize chitin-rich and other nonconventional substrates [41][42][43][44]. The sequenced C. oleaginosum strain is haploid, and similar in genome size and gene content to genomes from the sister order Tremellales, and this was also the case for several other Trichosporonales genomes that have since been sequenced [43,[45][46][47][48][49][50]. Interestingly, C. oleaginosum showed some similarities to C. neoformans in the organization of MAT loci.…”
mentioning
confidence: 92%
See 1 more Smart Citation